Koran Tempo's Innovation to Engage Gen Z Through Digitalization - Tri Widuri, Rachma; Nur Hidayat, Muhammad (KnE Social Sciences, 2024)
The development of digital technology in Indonesia has drastically changed people’s media behavior and habits. This change causes people to have two lives, namely real life and cyberspace. As a result, these changes are capable of producing technological disruptions. What has happened then is that new media have sprung up, especially online or cyber media. On the other hand, the number of print and radio media fell, while television media stagnated. Regarding these conditions, Koran Tempo, one of the business lines of the Tempo Media Group, inevitably has to innovate. As of January 1, 2021, this newspaper stops printing and switches to 100% digital form. This is done to outreach Gen Z and to have efficient business. This research tries to probe Koran Tempo’s strategy to attract the attention of Gen Z, through various digital innovations since the paper ceased publication in full on January 1, 2021. This study was conducted using qualitative methods and a case study approach. Primary data collection was carried out through interviews with the CEO, Board of Directors, Editor in Chief, and Senior Editors of Koran Tempo. Secondary data was collected through related references derived from books, online articles, and other research journals related to this study. This research shows that the program created by Koran Tempo has been proven to grab Gen Z through two types of innovations conducted by management, namely content innovation and design innovation. Keywords: Koran Tempo, digital, gen Z, innovation, media